The curious case of the rise in deflation expectations - Olivier Armantier; Gizem Koşar; Jason Somerville; Giorgio Topa; Wilbert Van der Klaauw; John C. Williams (Federal Reserve Bank of New York, 2022)
We study the behavior of U.S. consumers' inflation expectations during the high inflation period of 2021-22 using data from the Survey of Consumer Expectations. Short- and, to a lesser extent, mediumterm inflation expectations rose as inflation surged in 2021. Disagreement and uncertainty about future inflation increased significantly. Then, in 2022, even as inflation continued to climb, medium- and longerterm inflation expectations unexpectedly fell and medium- and longer-term deflation expectations increased. We find that respondents with deflation expectations tend to expect prices to mean revert and are more optimistic about the economic outlook.
Keywords: D12; D84; E31; E52; 330; inflation; deflation; expectations; consumer surveys